2015
DOI: 10.5301/jva.5000345
|View full text |Cite
|
Sign up to set email alerts
|

What is the Best Training for Vascular access Surgery?

Abstract: Questions have been raised whether there is a lack of appropriate training in access creation and maintenance, and if training juniors in arteriovenous (AV) fistulas may affect the outcome. A survey was undertaken to study "experts" opinion in access training using a closed questionnaire. The majority of "experts" consented that there is a lack of appropriate training in access creation and maintenance in a great extent, although they located the main deficit regarding access training in the preoperative plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…We have read with interest the letter by Aitken et al and we appreciate their constructive views as many of them are in agreement with our concepts expressed in our recent article on training in vascular access (1). However we believe they misunderstood our point regarding the effect of juniors’ training on outcome.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…We have read with interest the letter by Aitken et al and we appreciate their constructive views as many of them are in agreement with our concepts expressed in our recent article on training in vascular access (1). However we believe they misunderstood our point regarding the effect of juniors’ training on outcome.…”
supporting
confidence: 67%
“…We have never stated in our article that “training impacts negatively the service provision,” on the contrary we have proved that arteriovenous (AV) fistula creation is safe and of equal quality when delivered by residents. We came to this conclusion performing meta-analysis of all existing studies comparing the outcomes of AV fistulas created by consultants vs. trainees and getting no statistically significant results (1).…”
mentioning
confidence: 99%
“…A meta-analysis revealed that there is no difference in the outcome of AVFs created by trainees versus consultants, but it was mentioned that a successful access was based more in the preoperative planning rather than in technical surgical performance (19). In the study presented, there was a standardized preoperative clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…15 Apart from first-time fistulas in incident or prevalent CVC patients, expeditious but effective VA surgery requires that time and type of access, complicated redo operations salvaging failing, or managing failed fistulas are beyond the technical surgical performance of trainees and less experienced VA surgeons, potentially leading to suboptimal results. 16 Taking in aggregate, a low ''failure to save'' index (defined as the number of abandoned fistulas divided by the number of failing/failed and nonmatured ones within 6 weeks from creation) obtained in the pandemic period is the mirror of high performance quality in VA surgery because this index is less sensitive to patient-related factors than hospital/surgeon performances. 17 Besides VA saving issues, the meticulous planning and process of ''proper VA selection'' are fundamental to avoid type of accesses that will eventually not fulfill the needs of the patient's dialysis prescription leading to more future interventions 18 undesirable in this pandemic period.…”
Section: The ''Surgeon and Center Effect'' Phenomenonmentioning
confidence: 99%